2019
DOI: 10.21203/rs.2.16433/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meaningful Information in the Age of Big Data: A Scoping Review on Social Determinants of Health Data Collection for Electronic Health Records

Abstract: Background: Electronic Health Records (EHRs) are key tools for integrating patient data into health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, less complex classification methods have been used as well to identify specific groups of patients, risk assessment or aid in validating structured annotation 25–27. A recent scoping review found that although practitioners collect a variety of SBDH data at point of care through EHR, the overall use of automated technology is limited to date 28…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, less complex classification methods have been used as well to identify specific groups of patients, risk assessment or aid in validating structured annotation 25–27. A recent scoping review found that although practitioners collect a variety of SBDH data at point of care through EHR, the overall use of automated technology is limited to date 28…”
Section: Introductionmentioning
confidence: 99%
“…4 Given the significant impact on health outcomes, several large healthcare systems are taking steps to integrate SDOH screenings into the electronic medical record and to connect patients with local services. [5][6][7][8] Existing literature seeks to characterize SDOH and resource connection programs. In a systematic review of 37 socioeconomic needs programs, Gottlieb and colleagues included interventions that provided patients with community resources.…”
Section: Introductionmentioning
confidence: 99%